2019
DOI: 10.22159/ijap.2019v11i5.31638
|View full text |Cite
|
Sign up to set email alerts
|

Once Daily Immediate-and Extended-Release Bilayer Tablets of Etoricoxib: A Study on the Release Kinetics

Abstract: Objective: In the present work, the main objective was to develop bilayer extended release matrix tablets of etoricoxib by providing a loading dose followed by maintenance dose that expected to improve the therapeutic efficacy of the medication with less toxic effect. Methods: Bilayer tablets of etoricoxib was developed successfully with the meticulous proportion of release controlling Hydroxy propyl methyl cellulose K100 (HPMC K100) and lactose. The tablets were prepared by wet granulation technique. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Zero order First order Higuchi Hixon-Crowell Korsmeyer-peppas Comparing the R 2 values of all the formulations First order and Higuchi model showed the better fitting of data. The first order produced greater correlation of all formulations (R 2 =0.987 to 0.998 of) than all other models which indicated that the release of drug from the formulated tablets followed first order release kinetics that is the release is directly proportional to the concentration of the drug (10,11) .…”
Section: Formulationmentioning
confidence: 92%
See 3 more Smart Citations
“…Zero order First order Higuchi Hixon-Crowell Korsmeyer-peppas Comparing the R 2 values of all the formulations First order and Higuchi model showed the better fitting of data. The first order produced greater correlation of all formulations (R 2 =0.987 to 0.998 of) than all other models which indicated that the release of drug from the formulated tablets followed first order release kinetics that is the release is directly proportional to the concentration of the drug (10,11) .…”
Section: Formulationmentioning
confidence: 92%
“…The data obtained from the in vitro release study were analyzed using linear regression method according to the specified equations of zero order, first order, higuchi model, hixon-crowell model and korsmeyer-peppas model. Different plots were made such as cumulative % drug release vs. time (Zero order kinetic model); log cumulative of % drug remaining vs. time (First order kinetic model); cumulative % drug release vs. square root of time (Higuchi model); cube root of drug % remaining vs. time (Hixson-Crowell cube root law) and log cumulative % drug release vs. log time (Korsmeyer-Peppas model) (10,11) .…”
Section: Drug Release Kinetic Studymentioning
confidence: 99%
See 2 more Smart Citations